Detection and quantification of pathogens in saliva of adolescents with cerebral palsy: a cross-sectional study - Yoshida, Rosemeire Arai; Lobato, Tiago Bertola; Gorjão, Renata; França, Lucas Santiago; Alves, Lívia Araujo; Santos, Maria Teresa Botti Rodrigues (Frontiers in Dental Medicine, 2023)
Background: Elevated levels of inflammatory mediators in saliva have been described in individuals with cerebral palsy (CP).Objective: The aim of this study was to detect and quantify the pathogens Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum and Prevotella intermedia in the saliva of adolescents with CP.Methods: This is a cross-sectional study with adolescents with CP to detect periodontopathogens from saliva samples. Initially, saliva was collected from the CP (n=34) and control groups (n=31), followed by the gingival index (GI) for distribution of the groups of individuals with CP and control with gingivitis (bleeding on probing ≥ 10%) and without gingivitis. Bacterial DNA was extracted from saliva samples for detection of periodontopathogens by quantitative PCR (q-PCR). Data were analyzed by Mann Whitney and Kruskal-Wallis tests, analysis of variance t-test (ANOVA) with Tukey-Kramer post-hoc tests (p<0.05).The quantification of DNA of periodontopathogens in saliva samples showed that adolescents with CP present a variability (22.93 -39.56) in the detection of P. gingivalis and that some subjects with CP and gingivitis (n=4) present high quantification of P. gingivalis (ranging 39.56 -37,65), although no significant difference was found between the groups (p>0.05). A significant contrast was observed for the pathogen P. intermedia when comparing the difference in the control group (p = 0.0396). No major differences were detected in the quantification of periodontopathogens evaluated between the control group and CP.Adolescents with CP showed variability in the detection of DNA of periodontopathogens, especially a great variation in the detection of P gingivalis in saliva of CP with gingivitis.